NEGOTIATED MASCULINITIES. TRANS MEN’S ATTITUDES TOWARD DOMINANT NOTIONS OF MASCULINITY IN POLAND AND THE UNITED STATES - KŁONKOWSKA, ANNA M. (Society Register, 2021)
The paper is based on a qualitative research project carried out in Poland and the United States. It intends to compare the attitudes of trans men toward dominant notions of masculinity in their respective countries. Focusing on people who had been recognized as female at birth but whose experienced gender is male, the paper addresses their definitions of masculinity, attitudes toward accomplishing socially acknowledged patterns of maleness and re-defining their gender identity. For this purpose, the study compares the ways in which dominant models of masculinity are conceptualized by the research participants, their childhood socialization to locally and globally defined gender roles, the cultural context they grew up in, and its influence on negotiating one’s own gender identity. As a result, conclusions from the study present a comparison of Polish and US trans men’s efforts to negotiate personal and social identity in light of dominant masculine ideals (e.g., their potential reworking, acceptance, and rejection of various elements of those ideals and explore how alternative notions of masculinity shape different experiences of female-to-male transition in both countries.